Cancer in World Trade Center responders: Findings from multiple cohorts and options for future study. Issue 2 (4th January 2016) - Boffetta, Paolo; Zeig‐Owens, Rachel; Wallenstein, Sylvan; Li, Jiehui; Brackbill, Robert; Cone, James; Farfel, Mark; Holden, William; Lucchini, Roberto; Webber, Mayris P.; Prezant, David; Stellman, Steven D.
Abstract : Background: Three longitudinal studies of cancer incidence in varied populations of World Trade Center responders have been conducted. Methods: We compared the design and results of the three studies. Results: Separate analyses of these cohorts revealed excess cancer incidence in responders for all cancers combined and for cancers of the thyroid and prostate. Methodological dissimilarities included recruitment strategies, source of cohort members, demographic characteristics, overlap between cohorts, assessment of WTC and other occupational exposures and confounders, methods and duration of follow‐up, approaches for statistical analysis, and latency analyses. Conclusions: The presence of three cohorts strengthens the effort of identifying and quantifying the cancer risk; the heterogeneity in design might increase sensitivity to the identification of cancers potentially associated with exposure. The presence and magnitude of an increased cancer risk remains to be fully elucidated. Continued long‐term follow up with minimal longitudinal dropout is crucial to achieve this goal. Am. J. Ind. Med. 59:96–105, 2015. © 2015 Wiley Periodicals, Inc.